POULTRY COMPLEX: importance for brazilian agribusiness - Pereira, Elton Eduardo da Silva Brito; Brito, Carolina de Freitas; Edemar Ferrarezi Junior; Caracini, Luiz Gustavo (Revista Interface Tecnológica, 2023)
The production of broiler chickens is a fundamental activity in the agribusiness sector and plays a significant role in the formation of the Gross Domestic Product (GDP) of this area. Agribusiness encompasses all activities related to the production, processing and marketing of agricultural products, including the production of animals for human consumption, such as broilers. It is essential that the sector invest in sustainable technologies and practices, in order to guarantee its economic viability by minimizing environmental and social impacts. the broiler chicken chain is ahead of other chains of animals destined for meat, in relation to the percentage of contribution to the constitution of the GDP value, following its marketing course gaining space and market worldwide, and in this dispute of giants of the segment follows Brazil as the unrivaled exporter of this type of animal protein. This study is justified because the broiler chain is a segment of great economic importance for Brazil, in addition to ensuring food safety, promoting sustainability and providing studies and development in this sector. In this way, a bibliographical research was carried out, whose objective was to approach the poultry production chain of broilers and its economic importance in the composition of the GDP value for the Brazilian agribusiness. Thus demonstrating the economic importance of the poultry cutting chain in the formation of the Brazilian GDP.